The Shigella flexneri effector OspG interferes with innate immune responses by targeting ubiquitin-conjugating enzymes - Kim, Dong Wook (National Academy of Sciences, 2005)
Bacteria of Shigella spp. are responsible for shigellosis in humans. They use a type III secretion system to inject effector proteins into host cells and induce their entry into epithelial cells or trigger apoptosis in macrophages. We present evidence that the effector OspG is a protein kinase that binds various ubiquitinylated ubiquitin-conjugating enzymes, including UbcH5, which belongs to the stem cell factor SCF(β-TrCP) complex promoting ubiquitination of phosphorylated inhibitor of NF-κB type α (phospho-IκBα). Transfection experiments indicated that OspG can prevent phospho-IκBα degradation and NF-κB activation induced by TNF-α stimulation. Infection of epithelial cells by the S. flexneri wild-type strain, but not an ospG mutant, led to accumulation of phospho-IκBα, consistent with OspG inhibiting SCF(β-TrCP) activity. Upon infection of ileal loops in rabbits, the ospG mutant induced a stronger inflammatory response than the wild-type strain. This finding indicates that OspG negatively controls the host innate response induced by S. flexneri upon invasion of the epithelium.